Falls, Fear of Falling, Self‐Reported Impairments, and Walking Limitations in Persons With Late Effects of Polio. Issue 10 (26th April 2014) - Brogårdh, Christina; Lexell, Jan
Abstract : Objective: To investigate fall frequency during the past year, circumstances relating to falls, fear of falling, self‐reported impairments, and walking limitations in persons with mild to moderate late effects of polio. Design: A cross‐sectional postal survey. Participants: A total of 325 persons with clinically and electrophysiologically verified late effects of polio (175 women and 150 men; mean age 70 years). Method: Data regarding demographics, fall frequency during the past year, and circumstances relating to falls were obtained through a questionnaire. Fear of falling when performing daily activities was assessed with the Falls Efficacy Scale‐International (FES‐I), impairments were assessed with the Self‐Reported Impairments in Persons with Late Effects of Polio (SIPP), and walking limitations were assessed with the Walking Impact Scale (Walk‐12). Results: Of the 325 respondents, 62% reported at least one fall during the past year. Most of the falls were reported in the afternoon (68%) and when walking outdoors (53%). Persons who fell reported significantly higher ( P < .001) mean scores than did the persons who did not fall in the FES‐I (35.8 points versus 29.2 points), SIPP (28.2 points versus 25.0 points), and Walk‐12 (63% versus 43%). Conclusions: Falls are common in people with mild to moderate late effects of polio, especially later in the day and while walking outdoors. Fear of falling, self‐reported impairments, and walking limitations were greater among the persons who fell than in the persons who did not fall. To reduce falls and fear of falling in persons with late effects of polio and to increase their activity level and participation in various life situations, evidence‐based interdisciplinary fall management programs are needed.